Mechanisms of Allosteric Activation and Inhibition of the Deoxyribonucleoside Triphosphate Triphosphohydrolase from Enterococcus faecalis - Vorontsov, Ivan I. (American Society for Biochemistry and Molecular Biology, 2014)
EF1143 from Enterococcus faecalis, a life-threatening pathogen that is resistant to common antibiotics, is a homo-tetrameric deoxyribonucleoside triphosphate (dNTP) triphosphohydrolase (dNTPase), converting dNTPs into the deoxyribonucleosides and triphosphate. The dNTPase activity of EF1143 is regulated by canonical dNTPs, which simultaneously act as substrates and activity modulators. Previous crystal structures of apo-EF1143 and the protein bound to both dGTP and dATP suggested allosteric regulation of its enzymatic activity by dGTP binding at four identical allosteric sites. However, whether and how other canonical dNTPs regulate the enzyme activity was not defined. Here, we present the crystal structure of EF1143 in complex with dGTP and dTTP. The new structure reveals that the tetrameric EF1143 contains four additional secondary allosteric sites adjacent to the previously identified dGTP-binding primary regulatory sites. Structural and enzyme kinetic studies indicate that dGTP binding to the first allosteric site, with nanomolar affinity, is a prerequisite for substrate docking and hydrolysis. Then, the presence of a particular dNTP in the second site either enhances or inhibits the dNTPase activity of EF1143. Our results provide the first mechanistic insight into dNTP-mediated regulation of dNTPase activity.